EFFECT OF PC SIMULATION PROGRAM WITH INTEGRATED CIRCUIT EMPHASIS (PSPICE) ON STUDENT’S INTEREST IN CIRCUIT DESIGN IN FEDERAL COLLEGE OF EDUCATION, TECHNICAL OMOKU, RIVER STATE, NIGERIA - U. C. Nduka, Isaac (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The present study examined the effect of a PC simulation program with integrated circuit emphasis (PSPICE) on students' interest in Circuit Design at Federal College of Education, Technical Omoku, River State, Nigeria. One hundred and eighty-seven (n = 187) students enrolled in the engineering departments of the Federal College of Education, Technical Omoku, River State, Nigeria, comprising males and females between the ages of 23 and 31 years with a mean age of (M=9.14) and (SD= 1.24) were randomly selected as the study participants. They were assigned two conditions, with group A as the experimental condition. On the other hand, group B represents the control condition. A t-test analysis was performed on the data to answer the research question of whether the PSPICE simulation software would increase students' interest in circuit design. The analysis established a significant difference between the experimental and control conditions on interest in circuit design MD = 5.08, t (185) = 7.328, p = .000. Thus, the result provided the answer to the research question and suggested that the PSPICE software might be used to improve student's interest in circuit design. The practical implications and recommendations are discussed.